2014 International Conference on Intelligent Networking and Collaborative Systems 2014
DOI: 10.1109/incos.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Simulation of Distributed Large-Scale Critical Infrastructures

Abstract: The distributed and complexity nature of modern critical infrastructures that have to provide integrated services through the interoperability of heterogeneous subsystems, even spread among different countries, require new methodologies and tools to dominate overall systems complexity. In particular, in order to get knowledge about their real behavior and define dependability improvement actions, such complex and distributed systems should be reproduced and simulated locally. On the other hand, the extraordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The author shows how using SDN as a networking tool to create a virtual network infrastructure on a server that is used for quality assurance and testing, in order to ease network provisioning. Accordingly, Ficco et al [83] demonstrated how OpenFlow in test-beds for military use significantly reducing the costs of testing critical infrastructures.…”
Section: General Software Defined Network Applicationsmentioning
confidence: 99%
“…The author shows how using SDN as a networking tool to create a virtual network infrastructure on a server that is used for quality assurance and testing, in order to ease network provisioning. Accordingly, Ficco et al [83] demonstrated how OpenFlow in test-beds for military use significantly reducing the costs of testing critical infrastructures.…”
Section: General Software Defined Network Applicationsmentioning
confidence: 99%
“…The evaluation of complex systems requires a sophisticated modeling, simulation, and experimentation infrastructure, which requires the integration of existing simulation environments, real sub‐systems (usually Commercial Off‐The‐Shelf), and experimental platforms, which have to interact in a coordinated way. Therefore, specific hybrid and distributed modeling strategies, which integrate simulation and emulation environments, supported by novel technologies for resources virtualization and working environment reproduction, represent the most promising way to define the testing environment needed to support such complex paradigm .…”
Section: Introductionmentioning
confidence: 99%
“…There are no standards that exist for cross infrastructure modeling. In a coupled model, however, there are two widely accepted methods for exchanging information between simulations: the High Level Architecture HLA has been more widely used to implement distributed critical infrastructures such as air traffic control and vessel traffic systems [15]; electric grid and its SCADA systems [16]; and telecommunications, railway and electric systems [17]. A similar publish-subscribe communication paradigm is called Quality of Service Descriptors that has been implemented in a grid architecture for the electrical grid to aid in information sharing among critical infrastructures [18].…”
Section: Coupled Modelmentioning
confidence: 99%